Direction of Trade Statistics : March 2017. (Direction of Trade Statistics; Direction of Trade Statistics, 2017)
This paper discusses the coverage of Direction of Trade Statistics (DOTS) is augmented by using trade statistics available from other international organizations. Monthly data for all European Union member countries are sourced from the COMEXT database maintained by EUROSTAT. Annual data reported to the United Nations COMTRADE database are incorporated in DOTS for countries that do not report to the IMF. Furthermore, the availability of partner data makes it possible to calculate estimates of countries for which data are not obtainable from other sources. Estimation occurs if a reporting country does not report trade with its partners for a specific period. Data are estimated for all partners. In the absence of some or all of the monthly DOTS, quarterly or annual reported DOTS are used. Because imports are valued on a cost, insurance, and freight (CIF) basis and exports on a free on board (FOB) basis, the data are adjusted for the cost of freight and insurance.